Telaah Historisitas dan Penulisan Hadis Pada Masa Kenabian - Tasmin Tangngareng; Asmita; Rayyn, I Gusti Bagus Agung Perdana (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2026)
This article discusses the historicity and writing of hadith during the prophetic period. In this article, several important points will form the core of the discussion, namely the historicity of hadith during the prophetic period and the writing of hadith during the same period. It is therefore necessary to explain these matters to avoid confusion and misunderstanding regarding the historicity of hadith and the writing of hadith during the prophetic period. The study of this issue was conducted by conducting a literature review with a historical approach to the historical development of hadith studies. The conclusion is that during the time of the Prophet, known as 'Ashr al-Wahy wa al-Takwin, traditions were transmitted to the Companions through oral transmission, practice, and direct consent. In Arabian society where there was little tradition of writing, memorisation became the main means of transmission. The Prophet conveyed them in a contextual manner, both in public assemblies and in private. Although the writing of traditions was banned to preserve the purity of the Qur'an, some companions recorded them with the Prophet's permission. This prohibition was preventive in nature and was later replaced by the permission to write when the people were able to distinguish between the Qur'an and the hadith. The difference in the Prophet's attitude towards writing shows his caution in maintaining the authenticity of revelation. Thus, although not yet formally documented, hadith during the time of the Prophet was taught systematically and methodically